High-speed imaging database of water jet disintegration Part I: Quantitative imaging using liquid laser-induced fluorescence. (December 2021) - Roth, Adrian; Frantz, David; Chaze, William; Corber, Andrew; Berrocal, Edouard
Highlights: Observation of the transition between the Rayleigh to the atomization regime of a liquid jet captured at 50 000 fps. Generation of the largest high-speed image data of liquid jet disintegration freely available online. The liquid depth of liquid structures is quantified at high-speed using Laser-Induced Fluorescence. Two-views imaging has been applied providing a much more faithful representation of liquid breakups. The deformation and breakup of liquid blobs play an important role in the disintegration of liquid jets. Abstract: This paper is Part I in a series of articles focused on a fundamental study on liquid jet disintegration. The main goal of this work is to provide an extensive open access database of high-speed images and videos for modelers and researchers in the field of fluid mechanics studying the dynamics of a liquid jet transiting from the Rayleigh to the atomization regimes. The injector under examination has a single orifice 0.60 mm in diameter and was used to inject water into quiescent air at atmospheric temperature and pressure. In this study, only the liquid injection pressure was varied, reaching a maximum Reynolds number of approximately 60 000. Historically, high-speed videos of liquid jet disintegration have been captured via shadowgraphy imaging techniques. The alternate approach proposed here employs photographing a fluorescing liquid, using Laser Induced Fluorescence (LIF) allowing us to deduce the volume of the imaged liquid structures. The experiment is divided into two parts. In the first portion, the interrogation area measures a distance of 160 mm along the jet, and includes sets of 800 images, recorded at 40 000 frames per second, corresponding to a temporal resolution of 25 µs. In the second part, the viewable area was reduced to 28 mm, and 400 images were recorded at 50 000 frames per second resulting in a temporal resolution of 20 µs. This configuration enabled the finer structures of the jet to be resolved. In this case, two high-speed cameras orientated at 90˚ are used to simultaneously image the liquid jet. This two-angle detection configuration allows for the identification and more accurate account of the irregular liquid bodies formed in the jet. Descriptions of the optical arrangements, operating conditions, and the image post-processing methodologies used to obtain quantitative measurements of liquid depths from the LIF signal have been outlined. The resulting temporally resolved high-speed image series are openly downloadable on the website: https://spray-imaging.com/water-jet.html or alternatively on Open Science Framework at: https://doi.org/10.17605/OSF.IO/CG3DF